2020
DOI: 10.3390/molecules25235591
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Maillard Reaction, and Advanced Glycation End Product (AGE)-Receptor for AGE (RAGE) Signaling Inhibitors as Novel Therapeutic Strategies for Patients with AGE-Related Diseases

Abstract: Advanced glycation end products (AGEs) are generated by nonenzymatic modifications of macromolecules (proteins, lipids, and nucleic acids) by saccharides (glucose, fructose, and pentose) via Maillard reaction. The formed AGE molecules can be catabolized and cleared by glyoxalase I and II in renal proximal tubular cells. AGE-related diseases include physiological aging, neurodegenerative/neuroinflammatory diseases, diabetes mellitus (DM) and its complications, autoimmune/rheumatic inflammatory diseases, bone-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 159 publications
3
109
0
2
Order By: Relevance
“…MRPs lead to the formation of advanced-glycation (AGEs) and lipoxidation end products (ALEs) with proinflammatory activity. Moreover, MRPs could activate inflammatory responses via macrophages activation and immune dysfunction in helper T lymphocytes [ 55 ]. Therefore, all these studies could explain the loss of anti-inflammatory effects observed for HT30.…”
Section: Resultsmentioning
confidence: 99%
“…MRPs lead to the formation of advanced-glycation (AGEs) and lipoxidation end products (ALEs) with proinflammatory activity. Moreover, MRPs could activate inflammatory responses via macrophages activation and immune dysfunction in helper T lymphocytes [ 55 ]. Therefore, all these studies could explain the loss of anti-inflammatory effects observed for HT30.…”
Section: Resultsmentioning
confidence: 99%
“…AGEs refer to a kind of glycosylated molecules produced by oxidative stress or metabolism, which include not only cytokines but also some metabolites. After RAGE recognizes and binds to the corresponding ligand, it can activate the NF-κB pathway, thereby promoting the secretion of cytokines by inflammatory cells, such as IL-6 and TNF-α ( Shen et al, 2020 ). By the way, the activation of RAGE and NFκB also send a message to reactive oxidant species (ROS), a key role in oxidative stress, by NADPH oxidase ( Daffu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, these intermediate products may be further polymerized or reacted with amino acids and nucleic acids to form a variety of compounds collectively termed as advanced glycated end-products (AGEs). 3,29 The glycation process is shown in Figure 3. To date, many AGEs-modified proteins, such as hemoglobin, albumin, collagen, lens proteins,and erythrocyte membrane proteins, have been reported.…”
Section: Non-enzymatic Glycated Modification Of Tf and Related Diseasesmentioning
confidence: 99%
“…These pathways act in synergy on the nuclear factor NF-κB to induce the production and release of proinflammatory cytokines (TNF-α and IL-6), oxidative stress indicators (ROS), and pro-fibrotic cytokines (TGF-β and IL-13), thereby promoting the occurrence and development of diabetes and its complications. 29,54,58,59 Carboxymethyl lysine (CML) is one of the members of the AGEs family, which might interfere with the regulatory feedback mechanism of intracellular cholesterol to cause intracellular lipid accumulation and diabetic nephropathy, and AGEs inhibitor aminoguanidine hydrochloride may delay the progress of diabetic nephropathy. 60 Furthermore, AEGs overload is related to the occurrence of diabetic nephropathy, probably by interfering with the autophagy-lysosomal pathway.…”
Section: Molecular Mechanisms Of Non-enzymatic Glycated Tf In Diabetes and Diabetic Complicationsmentioning
confidence: 99%